Beijing temples and their social matrix – A GIS reconstruction of the 1912–1937 social scape. Issue 2 (2nd April 2016) - Zhang, Peiyao; Lin, Hui; Chitty, Naren; Cao, Kai
ABSTRACT: This paper reconstructs the spatial phenomena of Chinese temples in Beijing city during the Republican period (1912–1937). The research that informs the reconstruction is based on a Republican Beijing GIS data set that is focused on the transition of urban culture at that time. Spatial analytical methods based on GIS, including Standard Deviational Ellipse (SDE) and Geographically Weighted Regression (GWR), are used to demonstrate the distribution and change of Chinese temples in the 1920s and 1930s, and explore their interactions with population, industry-commerce, guild and church patterns. Overall, the Chinese temples have declined slightly during the period. The relations between Chinese temples and the selected factors exhibit spatial non-stationary across the city. This study highlights the importance of employing spatial and quantitative methods to yield a better understanding of the religious culture in Republican Beijing. Beijing is one of the top-tier political capitals of the world. Uncovering its historical geography is important to an understanding of the resilience of religion in a time where some religious revival is evident.